Health Financing Mechanisms, Access to Health and Economic Growth - Katja Bender (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2011)
The paper analyzes the comparative effects of alternative health financing mechanisms on economic growth within a two-sector model with human capital. The transitional growth effects of a social insurance system are stronger than those of an out-of-pocket payment system. A private health insurance system ranks 'in between'. If physical capital relative to health is abundant, investments in health have stronger growth effects, which points to the relevance of health investments in particular for developing countries. The relative advantage of a health financing system in the long run depends on the relative amount of investment in health within each system.
Keywords: E24; I15; H51; O11; O41; 330; Economic growth; Health; Health financing; Human capital; Social insurance; Gesundheitsfinanzierung; Gesetzliche Krankenversicherung; Wirtschaftswachstum; Entwicklungstheorie; Mehrsektoren-Modell; Theorie